Advantages of momentum work. I. Absolute time - Grit Kalies; Duong D. Do (AIP Advances)
This series presents the advantages of momentum work, a form of work that is missing in classical and quantum mechanics. In mechanics, forces are assumed to mediate interactions and actively change the properties of objects—an idea that is based on the kinematic concept of velocity and has led to indeterminacy at the quantum level and to spacetime theories at the macrolevel, according to which space and time are relative. A different picture emerges when only processes with energy transfer, including a form of work that changes the momentum of objects, can change the properties of objects, even at the quantum level. The aim of this series is to show that the priority of processes over forces leads to a vivid and deterministic description of the temporal behavior of matter in Euclidean space. In this first paper of the series, we address the conceptual content of basic variables, with a focus on velocity. When velocity is treated as a dynamic state variable of a material object, rather than a kinematic quantity, absolute time and absolute simultaneity are an imperative logical consequence.